PREVALENCE AND COMPARISON BETWEEN THE EFFICACY OF DIFFERENT TECHNIQUES FOR DIAGNOSIS OF TOXOPLASMA GONDII AMONG WOMEN IN ERBIL PROVINCE-IRAQI KURDISTAN - Hamad, Narmin R.; Kadir, Mohammed A. (European Scientific Journal, ESJ, 2014)
Introduction: Toxoplasmosis is one of the most common social and gynecological problems in Iraq. Materials and Methods: This study investigated the prevalence of Toxoplasma gondii among females attending the gynaecological out patient’s clinics in Maternity and Rizgary hospitals, several health centers and some private clinics in Erbil-Iraqi Kurdistan, from 16th July 2007 till 15th July 2008, by using different diagnostic methods. Serological diagnosis was done using LAT, ELISA-IgM and IgG tests and 2ME method, for investigation of T. gondii seroprevalence, in relation with residency, marital status, age, education, occupation, gestation, frequency of abortion and infertility. Results: The rate of Toxoplasma seropositivity, was higher using LAT 54.46%, followed by ELISA IgG 37.5%, 2ME 14.29% and ELISA IgM 9.13%, and higher rates were recorded among rural inhabitants in comparison with those living in urban areas. The rate of Toxoplasma seropositivity was highest among married women, and the age group 47-57 years revealed highest infection rate. The higher rates were indicated among the housewives than the employers. The pregnant women have higher seroprevalence rate than non-pregnant patients. Women with more than three abortions showed the higher rate of seropositive antibodies. Conclusions: Significant difference was recorded between the techniques and seropositivity of T. gondii antibodies which was higher by LAT than ELISA-IgG, ELISA IgM and 2ME.